Hepcidin in the diagnosis of iron disorders - Girelli, Domenico; Nemeth, Elizabeta; Swinkels, Dorine W. (Blood, 2016)
The discovery of the iron-regulatory hormone hepcidin in 2001 has revolutionized our understanding of iron disorders, and its measurement should advance diagnosis/treatment of these conditions. Although several assays have been developed, a gold standard is still lacking, and efforts toward harmonization are ongoing. Nevertheless, promising applications can already be glimpsed, ranging from the use of hepcidin levels for diagnosing iron-refractory iron deficiency anemia to global health applications such as guiding safe iron supplementation in developing countries with high infection burden.